Using Taguchi method for the optimization of processing variables to prepare porous scaffolds by combined melt mixing/particulate leaching. (5th October 2017) - Scaffaro, Roberto; Sutera, Fiorenza; Lopresti, Francesco
Abstract: Synthetic biopolymers have made significant inroads into the development of devices for tissue regeneration. In this context, a challenge is the achievement of appropriate properties mimicking the natural extracellular matrix by fabricating scaffolds presenting mechanical properties, specific surface, porosity and pore interconnection adequate for the final application. This study involved a systematic procedure based on Taguchi method for parameters optimization of melt mixing/particulate leaching combined processes aiming to enhance the performance of the scaffolds. In particular, it was evaluated the effect of time and temperature of melt mixing of the poly(lactic acid) matrix with two water-soluble inorganic porogen agents (i.e. NaCl or CaCl2 ) with two different pore size and poly(ethylene glycol). Thereafter, the blends were compression molded and water-leached for different time and at different pH. By adopting L8 Taguchi orthogonal array, seven control factors, each at two levels, were tested, and ANOVA was applied to find the statistically significant factors and the combination of their optimal levels. The results revealed that the mixing temperature had the highest effect on mechanical properties. Moreover, the internal architecture of the scaffolds was studied by morphological analysis, finding that it is affected by the kind of porogen salt and by mixing time. Graphical abstract: Highlights: Polylactic acid porous scaffolds were successfully fabricated by combining melt mixing and particulate leaching. Mixing temperature and time are the most significant variable affecting mechanical properties of the scaffolds. Pores morphology was found to be affected by the kind of porogen salt (i.e. NaCl or CaCl2 ) and their dimension.